A phase II trial of high‐dose intravenous interferon alpha‐2 in advanced colorectal cancer - Silgals, Robert M.; Ahlgren, James D.; Neefe, John R.; Rothman, John; Rudnick, Seth; Galicky, F. Peter; Schein, Philip S. (Cancer, 1984)
Twenty‐one patients with metastatic colorectal cancer were treated with high‐dose intravenous interferon alpha‐2 (30–50 × 106 units/m2) administered daily for 5 consecutive days. Courses of therapy were repeated every 2 to 3 weeks. No tumor responses were seen among 15 evaluable patients. In two subjects, disease remained stable for 3 and 7 months, respectively. Toxicity was substantial and a de‐escalation of dose was frequently required. Fevers, gastrointestinal symptoms, fatigue, leukopenia, and elevated serum transaminases were common. High‐dose interferon was found to be ineffective in the treatment of metastatic colorectal cancer. A daily dose of 50 × 106 units/m2 was greater than the maximum tolerated dose in this group of patients.